ChemInform Abstract: Two‐Step Pressure‐Induced Superhydration in Small Pore Natrolite with Divalent Extra‐Framework Cations. Issue 31 (August 2015) - Seoung, Donghoon; Lee, Yongmoon; Kao, Chi‐Chang; Vogt, Thomas; Lee, Yongjae
Abstract K‐natrolite is prepared by combining a 4 M KNO3 solution with the natural mineral Na16Al16Si24O80 ·16H2O in a 100:1 weight ratio for 24 h.